Quality Improvement in Inflammatory Bowel Disease - Melmed, Gil Y. (Millennium Medical Publishing, 2013)
Chronic illnesses such as inflammatory bowel disease (IBD) present a unique opportunity to define and improve the quality of care. Processes of care can be complex, and outcomes of care may vary across different healthcare delivery settings. Patients with IBD are managed over long periods of time and often by the same physician within a single care delivery system. Both patients with Crohn’s disease and ulcerative colitis have variable courses of disease progression that require changes in therapy over time. These factors necessitate multiple areas of potential assessment and improvement of processes and outcomes of care. A current initiative is the development of quality measures. The American Gastroenterological Association has developed accountability measures for the Physician Quality Reporting System, and the Crohn’s and Colitis Foundation of America has developed a set of top 10 recommended processes and outcomes of measurement for high-quality care of patients with IBD. In addition, the pediatric ImproveCareNow collaborative network has collected improvement data from dozens of pediatric centers over the past 5 years and has demonstrated improvement in overall disease activity in their cohort through iterative quality improvement processes. Future directions for quality indicators for adults with IBD will involve implementation of quality-measure reporting, both for purposes of reimbursement as well as improvement of care. These strategies will need to be closely monitored to evaluate the effect of improvement programs on outcomes.